2020
DOI: 10.1111/eci.13463
|View full text |Cite
|
Sign up to set email alerts
|

Higher ACE2 expression levels in epicardial cells than subcutaneous stromal cells from patients with cardiovascular disease: Diabetes and obesity as possible enhancer

Abstract: Aims Obesity, diabetes and cardiovascular disease are associated with COVID‐19 risk and severity. Because epicardial adipose tissue (EAT) expresses ACE2, we wanted to identify the main factors associated with ACE2 levels and its cleavage enzyme, ADAM17, in epicardial fat. Materials and methods Epicardial and subcutaneous fat biopsies were obtained from 43 patients who underwent open‐heart surgery. From 36 patients, biopsies were used for RNA expression analysis by real‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
(70 reference statements)
2
24
0
Order By: Relevance
“…A study on EAT and SAT biopsies from 43 patients who underwent open-heart surgery identified higher levels of ACE2 (p < 0.05) but lower ADAM-17 (p < 0.001), with its cleavage enzyme in EAT compared with subcutaneous fat. Obesity and T2D exacerbated this difference in patients with cardiovascular disease (103). In an animal study, ACE2 was upregulated in murine EAT in association with highfat diet.…”
Section: Visceral Adipose Tissue and Epicardial Adipose Tissue As Markers Of Myocardial Injurymentioning
confidence: 96%
“…A study on EAT and SAT biopsies from 43 patients who underwent open-heart surgery identified higher levels of ACE2 (p < 0.05) but lower ADAM-17 (p < 0.001), with its cleavage enzyme in EAT compared with subcutaneous fat. Obesity and T2D exacerbated this difference in patients with cardiovascular disease (103). In an animal study, ACE2 was upregulated in murine EAT in association with highfat diet.…”
Section: Visceral Adipose Tissue and Epicardial Adipose Tissue As Markers Of Myocardial Injurymentioning
confidence: 96%
“…Angiotensin-converting enzyme 2 (ACE2), which is widely recognized as the entry receptor for SARS-CoV-2 into host cells 152 , is expressed in human EAT 133 . The downregulation of ACE2 levels increases EAT inflammation, whereas treatment with angiotensin 1–7 reduced EAT inflammatory cytokines in a mouse model 153 .…”
Section: Eat and Covid-19mentioning
confidence: 99%
“…This is not to be equated with enzyme activity. However, other studies have also investigated ADAM10 and ADAM17 only on gene expression level, as evidence suggests that their gene expression correlates with their activity (Kinoshita et al, 2013;Cheng et al, 2021;Couselo-Seijas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%